Paleoseismic evidence of clustered earthquakes on the San Andreas fault in the Carrizo Plain, California - Sieh, Kerry (2012)
Exposures we have excavated across the San Andreas fault contradict the hypothesis that part of the fault in the Carrizo Plain is unusually strong and experiences relatively infrequent rupture. The exposures record evidence of at least seven surface-rupturing earthquakes which have been approximately dated by accelerated mass spectrometry radiocarbon analysis of detrital charcoal and buried in situ plants. Five large earthquakes have occurred since 1218 A.D. The most recent earthquake, event A, was the 1857 Fort Tejon earthquake, which we have associated with 6.6–10 m of dextral slip along the main fault trace. The penultimate earthquake, event B, most likely occurred within the period A.D. 1405–1510. Slip from either events B and C combined or from event B alone, totals 7–11 m. Three earthquakes, events C, D, and E, occurred in a temporal cluster prior to event B and after approximately A.D. 1218. The average recurrence interval within this cluster is 73–116 years, depending on assumptions. Events F and G occurred after 200 years B.C. A depositional hiatus between events E and F may hide evidence of additional earthquakes. Events B and D within the Carrizo cluster of A.D. 1218–1510 may correlate with events T (A.D. 1329–1363) and V (A.D. 1465–1495) at Pallett Creek on the Mojave “segment” of the fault. This suggests two fault ruptures similar in length to that of 1857. Events C and E apparently did not rupture the Mojave section, which suggests that the Carrizo segment has ruptured independently or in combination with segments to the north. Irregular repeat times of large earthquakes suggest a pattern of clustered events at the end of seismic “supercycles.”